An Analysis of The Students’ Speaking Mastery Through The Speech Extracurricular Activity at MTs Nu Malintang Jae - Atikah, Luri; Hasibuan, Sri Wahyuni; Yahsya, Akhrif (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Limited public speaking Mastery among students highlight the need for structured guidance and continuous practice. To address this issue, MTs. NU Malintang Jae implemented a speech extracurricular activity as a platform to enhance students’ speaking Mastery. This study aimed to analyze students' speaking skills and identify the challenges they faced during the activity. A qualitative field study method was used, involving 25 eighth-grade students. Data were collected through interviews, observations, and documentation. The analysis involved data reduction, data presentation, and conclusion drawing. The findings showed that 52% of students had a